2004
DOI: 10.1212/01.wnl.0000145772.77040.24
|View full text |Cite
|
Sign up to set email alerts
|

The covert priming effect of faces in prosopagnosia

Abstract: Direct and indirect covert functions likely share similar mechanisms in patients with apperceptive prosopagnosia and may reflect residual activity in anterior and left hemispheric components of the normal face-processing network. However, face priming may be ineffectual in patients with severely degraded facial memories from anterior temporal damage. This may indicate a difference between residual patterns of face-related activity in associative and apperceptive prosopagnosia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 38 publications
2
19
1
Order By: Relevance
“…'s impairment were gained by assessing her ability to process faces implicitly, that is, without awareness of the face identity. There is evidence that at least some, if not all, neurological patients who acquire prosopagnosia after brain injury covertly respond to the identity of faces they knew before injury (Barton, Cherkasova, & Hefter, 2004;De Haan, Bauer, & Greve, 1992;De Haan et al, 1987). In contrast, as reported with other prosopagnosics before her (Barton, Cherkasova, & O'Connor, 2001;Bentin et al, 1999; but see Jones & Tranel, 2001, for an exceptional case), we found no evidence for covert face identification in K.W.…”
Section: Face Processingcontrasting
confidence: 58%
“…'s impairment were gained by assessing her ability to process faces implicitly, that is, without awareness of the face identity. There is evidence that at least some, if not all, neurological patients who acquire prosopagnosia after brain injury covertly respond to the identity of faces they knew before injury (Barton, Cherkasova, & Hefter, 2004;De Haan, Bauer, & Greve, 1992;De Haan et al, 1987). In contrast, as reported with other prosopagnosics before her (Barton, Cherkasova, & O'Connor, 2001;Bentin et al, 1999; but see Jones & Tranel, 2001, for an exceptional case), we found no evidence for covert face identification in K.W.…”
Section: Face Processingcontrasting
confidence: 58%
“…Clinicians may confuse DP with the face-processing impairment seen in individuals with autism spectrum disorder (Wilson et al, 2010). Although two of our five participants with DP had a history of social isolation, language delay, or hyperlexia, none had been diagnosed with autism or had elevated Autism Quotient scores, and all were independent adults with normal relationships and successful jobs or careers (Barton et al, 2004a; Duchaine and Nakayama, 2004, 2006a). …”
Section: Discussionmentioning
confidence: 99%
“…Representative MRI scans are shown in Figure 1, and anatomic templates in Figure 2. More detailed case information on most of these subjects can be found in previous reports using the same subject identification numbers (Barton et al, 2004a,Barton et al, 2004b,Barton and Cherkasova, 2005.…”
Section: Methodsmentioning
confidence: 99%